Ein Junge aus Alaska - Kendall, Russ (Carlsen, 1995)
Describes, in text and photographs, the home, family, school, and day-to-day life of a seven-year-old Eskimo boy living in a small village in Alaska.
Keywords: Kindersachbuch; Indianer; Eskimos; German language materials; Indians of North America; Inuit; Eskimo